Impact of Customer’s Impulsivity and Marketing Cues to Purchase Decision of Beverage Product Category - Prawono, Desi Ambar; ., Mia Tantri Diah Indriani (Journal of Economics and Behavioral Studies, 2013)
The research was conducted to explore consumer impulsivity and impulsive buying toward beverages product. In addition, in subsequent analysis, it also applies Consumer Decision Journey into impulsive buying behavior on beverage products. The analysis explains which marketing cues acts as most influential factors in such purchase behavior. Questionnaire was designed based on valid scale borrowed from previous research. A total of 105 respondents participated in this research. Questionnaire was distributed directly and by electronic mail. Based on the analysis, consumer only exercises impulsive buying on green tea and ready to drink tea category. Past experience and WOM are the most influencing factors in each step of the customer decision journey. Implications of this research are useful for FMCG marketers in improving marketing cues.